Clinical Guidelines of the Egyptian Psychiatric Association for the Management of Treatment-Resistant Unipolar Depression in Egypt - Abdel-Wahab, Momtaz; Okasha, Tarek; Shaheen, Mostafa; Nasr, Mohamed; Molokheya, Tarek; Omar, Abd ElNasser; Rabie, Menan A.; Samy, Victor; Hamed, Hany; Ali, Mohamed (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder is a public health burden that creates a strain not only on individuals, but also on the economy. Treatment-resistant depression is a condition that results from inadequate response to antidepressant medications. Objective/Hypothesis: To develop a treatment guideline for Treatment Resistant Depression (TRD). Methodology: Experts in the field gathered and reviewed the available evidence about the subject. Then, a series of meetings were held to create recommendations that can be utilized by Egyptian psychiatrists. Results: The guidelines provide recommendations in various clinical settings. It evaluates different situations, such as patients at risk of resistance, those with resistance and recommends strategies to resolve the clinical case. Conclusion: The consensus guidelines will improve the outcomes of patients, as they provide recommendations across various domains that are of concern for the practicing psychiatrist.